Raquianestesia contínua em paciente submetido à gastrectomia parcial. Relato de caso - Pitombo, Patrícia Falcão [UNESP]; Moura, Robson; Miranda, Ricardo (Elsevier, 2009)
BACKGROUND AND OBJECTIVES: Due to the high incidence of technical and neurological complications, continuous spinal blocks were not performed for several years. With the advent of intermediate catheters the technique has been used more often and gaining acceptance among anesthesiologists. The objective of this report was to demonstrate the usefulness of the technique as a viable alternative for medium and major size surgeries. CASE REPORT: This is a 58 years old female patient, weighing 62 kg, physical status ASA I, with a history of migraines, low back pain, and prior surgeries under spinal block without intercurrence. The patient was scheduled for exploratory laparotomy for a probable pelvic tumor. After venoclysis with an 18G catheter, monitoring with cardioscope, non-invasive blood pressure and pulse oximetry was instituted; she was sedated with 2 mg of midazolam and 100 μg of fentanyl, and placed in left lateral decubitus. The patient underwent continuous spinal block through the median approach in L 3-L 4; 9 mg of 0.5% hyperbaric bupivacaine and 120 μ g of morphine sulfate were administered. Inspection of the abdominal cavity revealed a gastric stromal tumor that required an increase in the incision for a partial gastrectomy. A small dose of hyperbaric solution was required for the entire procedure, which was associated with complete hemodynamic stability. Postoperative admission to the ICU was not necessary; the patient presented a good evolution without complaints and with a high degree of satisfaction. She was discharged from the hospital after 72 hours without intercurrence. CONCLUSIONS: Intermediate catheters used in continuous spinal blocks have shown the potential to turn it an attractive and useful technique in medium and large size surgeries and it can even be an effective alternative in the management of critical patients to whom hemodynamic repercussions can be harmful.
Continuous spinal block in a patient undergoing partial gastrectomy. Case report
Keywords: Anesthetic techniques, regional: subarachnoid; Surgery, abdominal: gastrectomy; bupivacaine; morphine sulfate; adult; case report; decubitus; female; hemodynamics; human; laparotomy; partial gastrectomy; pelvis tumor; peritoneal cavity; spinal anesthesia; stomach tumor; stroma; Anesthesia, Spinal; Female; Gastrectomy; Humans; Middle Aged